Ultrasound-sensitive cRGD-modified liposomes as a novel drug delivery system - AlSawaftah, Nour Majdi (2022)
Targeted liposomes enable the delivery of encapsulated chemotherapeutics to tumours by targeting specific receptors overexpressed on the surfaces of cancer cells; this helps in reducing the systemic side effects associated with the cytotoxic agents. Upon reaching the targeted site, these liposomes can be triggered to release their payloads using internal or external triggers. In this study, we investigate the use of low-frequency ultrasound as an external modality to trigger the release of a model drug (calcein) from non-targeted and targeted pegylated liposomes modified with cyclic arginine–glycine–aspartate (cRGD). Liposomes were exposed to sonication at 20-kHz using three different power densities (6.2, 9, and 10 mW/cm²). Our results showed that increasing the power density increased calcein release from the sonicated liposomes. Moreover, cRGD conjugation to the surface of the liposomes rendered cRGD-liposomes more susceptible to ultrasound compared to the non-targeted liposomes. cRGD conjugation was also found to increase cellular uptake of calcein by human colorectal carcinoma (HCT116) cells which were further enhanced following sonicating the cells with low-frequency ultrasound (LFUS).